In Vitro Culture and Symbiotic Relationships of Paphiopedilum Niveum, Taeniophyllum Obtusum and Vanda Hookeriana with Their Associated Fungi - Irawati (1987)
In vitro cultures of three orchid species, namely, Paphiopedilum niveum, Taeniophyllum obtusum and Yanda hookeriana, were initiated from different parts of the plants. Proliferous protocorm-like bodies were obtained from shoot tips and axillary buds of V. hookeriana and shoot tips and in florescence of T. obtusum. Shoot tips and axillary buds of P. niveum grew into single or multiple plantlets. In florescence culture of T. obtusum developed into multiple branches of in florescences, calli or produced roots. Young leaf tip or leaf base of P. niveum and root of T. obtusum were unable to differentiate into callus. However, culture of young flower bud of P. niveum produced leaf after seven months. High pH of the medium was suitable for T. obtusum cultures. Low concentration of modified Knudson's C medium was preferable to the standard concentration for the culture of P. niveum.